Revisiting the relationship between impulsivity, apathy, and action control: Bayesian inference from a stop-signal task study - Emma Michel; Axel Garnier-Allain; Mariia Kaliuzhna; Djamila Bennabi; Mathieu Servant; Matthieu Béreau (PLoS ONE, 2026)
Apathy and impulsivity are multidimensional constructs that shape goal-directed behavior. Although the motivational dopaminergic spectrum hypothesis frames them as opposing ends of a single continuum, questionnaire-based studies consistently show that they positively co-occur in both healthy and clinical populations. An emerging theoretical resolution of this paradox is that apathy and impulsivity relate to distinct components of goal-directed behavior, with co-occurrence potentially arising from domain-general factors and/or partially overlapping neurophysiological networks. Here, we examined this proposal in the domain of action control using the stop-signal task, which provides separable indices of action inhibition (stop-signal response time, SSRT) and action initiation (go response time, goRT) within the independent race model. Based on prior findings and theoretical considerations, we expected SSRT to covary with urgency-related impulsivity and goRT with action-initiation apathy. A large sample of healthy young adults (N = 144) completed a stop-signal task implemented in accordance with consensus recommendations, alongside validated multidimensional measures of impulsivity (UPPS-P impulsive behavior scale) and apathy (Lille Apathy Rating Scale). Bayesian analyses replicated a positive association between global apathy and impulsivity scores. However, SSRT was not associated with urgency, and goRT was not associated with action-initiation apathy, with moderate evidence for the null. Additional exploratory analyses provided moderate evidence against the majority of correlations between stop-signal indices and the remaining scale dimensions, including global scores. Thus, stop-signal indices did not dissociate apathy and impulsivity in action control, highlighting limits of task-based accounts of their co-occurrence.